A revision of the Neotropical species of Lucilia Robineau-Desvoidy (Diptera: Calliphoridae) - Whitworth, Terry (Zootaxa, 2014)
A key to 23 species of Neotropical Lucilia, including six new species is given. Information is provided on all known Lucilia species found in the region, including the West Indies, Galápagos Islands, and Central and South America. The following six new species are described based on the examination of over 2700 adult specimens from Central and South America: Lucilia albofusca sp. nov. from southern Central America and northern South America, Lucilia nitida sp. nov. from Brazil, Peru and Venezuela, Lucilia pulverulenta sp. nov. from Central America (Honduras south to Panama) and South America (Colombia and Ecuador), Lucilia rognesi sp. nov. from Costa Rica, Honduras and Panama, Lucilia vulgata sp. nov. from South America (widespread from Venezuela to Argentina), and Lucilia woodi sp. nov. from Central America (Honduras south to Panama). The status of Phaenicia japuhybensis Mello, 1961 is clarified; it is considered a valid species of Lucilia. Musca ochricornis Wiedemann, 1830 is removed from its current synonymy with Musca eximia Wiedemann, 1819 and considered a valid species of Lucilia. Lucilia mera Shannon & Del Ponte, 1926 and L. primaveris Shannon & Del Ponte, 1926 are synonymized with L. ochricornis, syn. nov. Lucilia littoralis Blanchard 1938 is synonymized with L. eximia (Wiedemann, 1819), syn. nov. Lectotypes are designated for L. mera, L. primaveris, and L. ochricornis.